International Reference Ionosphere 2016: From ionospheric climate to real‐time weather predictions. Issue 2 (27th February 2017) - Bilitza, D.; Altadill, D.; Truhlik, V.; Shubin, V.; Galkin, I.; Reinisch, B.; Huang, X.
Abstract: The paper presents the latest version of the International Reference Ionosphere model (IRI‐2016) describing the most important changes and improvements that were included with this version and discussing their impact on the IRI predictions of ionospheric parameters. IRI‐2016 includes two new model options for the F 2 peak height hm F 2 and a better representation of topside ion densities at very low and high solar activities. In addition, a number of smaller changes were made concerning the use of solar indices and the speedup of the computer program. We also review the latest developments toward a Real‐Time IRI. The goal is to progress from predicting climatology to describing the real‐time weather conditions in the ionosphere. Key Points: New models for the F 2 peak height hm F 2 in IRI‐2016 Development of the Real‐Time International Reference Ionosphere (IRI) Improved description of IRI ion composition at low and high solar activities